Lertal®, a multicomponent nutraceutical, could reduce the use of antihistamines in children with allergic rhinoconjunctivitis - Tosca, Maria Angela; Olcese, Roberta; Marinelli, Guido; Papale, Maria; Zicari, Anna Maria; Marseglia, Gianluigi; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2020)
Antihistamines are the cornerstone treatment of allergic rhinitis (AR). To quantify the antihistaminic consume is particularly relevant in clinical practice, since a remarkable use is usually associated with severe symptoms. The aim of the study was to measure the use of antihistamines in two groups of children suffering from AR. The first group took a course of a nutraceutical (Lertal®) before the observation (active group, AG); a second one was considered as control (control group, CG). Both groups took antihistamines on demand. The children were visited at baseline and after 1 year. The number of days of antihistaminic use was the primary outcome. Children in AG had a significant reduced number of antihistamines use in comparison with CG (p=0.008). In conclusion, the current study showed that a course with a multicomponent nutraceutical could reduce the use of symptomatic antihistamines in children with allergic rhinoconjuncti- vitis.